Dynamic Free Riding with Irreversible Investments - Battaglini, Marco; Nunnari, Salvatore; Palfrey, Thomas R. (American Economic Review, 2014)
We study the Markov equilibria of a model of free riding in which n infinitely lived agents choose between private consumption and irreversible contributions to a durable public good. We show that the set of equilibrium steady states converges to a unique point as depreciation converges to zero. For any level of depreciation, moreover, the highest steady state converges to the efficient level as agents become increasingly patient. These results are in contrast to the case with reversible investments, where a continuum of inefficient equilibrium steady states exists for any level of depreciation, discount factor, and size of population. (JEL D11, H41)